2018
DOI: 10.15666/aeer/1604_40654080
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock Influences on Seasonal Changes in Leaf Physiology and Fruit Quality of Rio Red Grapefruit Variety

Abstract: Citrus is a conventionally produced fruit crop in extensive agricultural areas in Mediterraneantype agroecosystems. The use of rootstocks for citrus fruits is necessary for profitable production under some limiting factors, such as climactic factors, bad soil conditions, and diseases. In addition, the use of the citrus rootstocks provides a large number of choices to growers to increase fruit quality and yield, obtain early fruiting, uniform cropping and high-density planting, avoid juvenility, and control tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…As in other studies [11,13,37], the results revealed an effect of citrus rootstocks on yield (kg tree −1 ; Table 4). Thus, 'Lane Late' trees on MP recorded higher yields (60.93 kg tree −1 ), which were statistically significant in most growing seasons, while 'Lane Late' trees on FA13 (32.44 kg tree −1 ) and FA41 (36.85 kg tree −1 ) had almost always the lowest yield.…”
Section: 'Lane Late' Navel Orange Trees Productivitysupporting
confidence: 83%
See 2 more Smart Citations
“…As in other studies [11,13,37], the results revealed an effect of citrus rootstocks on yield (kg tree −1 ; Table 4). Thus, 'Lane Late' trees on MP recorded higher yields (60.93 kg tree −1 ), which were statistically significant in most growing seasons, while 'Lane Late' trees on FA13 (32.44 kg tree −1 ) and FA41 (36.85 kg tree −1 ) had almost always the lowest yield.…”
Section: 'Lane Late' Navel Orange Trees Productivitysupporting
confidence: 83%
“…In sustainable plantation systems, the use of citrus rootstocks with a higher ability to uptake and translocate soil nutrients could be used as an important tool to reduce the use of chemical fertilizers. Citrus rootstocks are known to have an effect on performance and plant nutrient status [9,[11][12][13]. A significant effect of the rootstocks (p < 0.05) was found in certain macro-nutrients' concentrations of 'Lane Late' leaves (Table 5).…”
Section: 'Lane Late' Navel Orange Trees Nutrient Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient management is one of the most important factors in citrus production as it directly influences tree health and productivity (Galvez-Sola et al, 2015;Morgan & Graham, 2019). The plant nutrient status is influenced by the nutrient uptake efficiency of the plant, which is affected by many factors including rootstock cultivar (Uygur & Yetisir, 2009;Toplu et al, 2011;Yilmaz et al, 2018), soil type, season and plant developmental stage (Scagel et al, 2007) as well as soil-borne and other diseases such as huanglongbing (Cao et al, 2015;Morgan & Graham, 2019). To determine the nutrient status of a plant and correct potential deficiencies, regular analysis of leaf nutrient concentrations is essential (Galvez-Sola et al, 2015;Stammer & Mallarino, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, an increase in leaf K content increases rind thickness and coarseness (Chapman, 1968). Although it is known that rootstock influences nutrient uptake (Legua et al, 2013;Zambrosi, Mesquita, Tanaka, Quaggio & Mattos, 2013;Yilmaz, Cimen, Incesu, Uysal Kamiloglu & Yesiloglu, 2018), very few studies report the influence of rootstock on peel thickness and its nutritional composition. In 'Nova' mandarin, this correlation was observed in the fruit from rootstock Troyer citrange with the thinnest peel, where tree leaves had the largest amounts of P and the least amounts of K (Georgiou, 2000).…”
Section: Peel Thicknessmentioning
confidence: 99%